Photoinduced effects in l-alanine crystals - Wojciechowski, A.; Ozga, K.; Ali H., Reshak Al-Jaary; Miedzinski, R.; Berdowski, J.; Tylczyński, Z. (Elsevier B.V., 2010)
Link to publisher's homepage at http://www.elsevier.com/